Front Cover: Artificial Supramolecular Pumps Powered by Light (Chem. Eur. J. 43/2021). Issue 43 (26th June 2021) - Corra, Stefano; Casimiro, Lorenzo; Baroncini, Massimo; Groppi, Jessica; La Rosa, Marcello; Tranfić Bakić, Marina; Silvi, Serena; Credi, Alberto
Abstract : Light‐driven supramolecular pumping was achieved, as a result of unidirectional threading and dethreading movements, by combining photoisomerization and self‐assembly processes in a closed reaction network (represented by reservoirs and pipes in the cover image). While light irradiation (bulb and gears) pushes the species energetically uphill, subsequent exergonic reactions (falling water) convert energy into motion, and a continuous and directional transfer along the cycle (the water flow) is observed at the photostationary state. Artwork by Stefano Corra. More information can be found in the Full Paper by A. Credi et al. (DOI: 10.1002/chem.202101163 ).